2020
DOI: 10.1016/j.compgeo.2020.103710
|View full text |Cite
|
Sign up to set email alerts
|

DEM modelling to assess internal stability of gap-graded assemblies of spherical particles under various relative densities, fine contents and gap ratios

Abstract: It is believed that the relative density (Dr) can affect the internal stability of the gap-graded soils and hence the erosion of their fine particles (i.e. susceptibility to suffusion). This paper investigates the influence of Dr on the contribution of fine particles on soil fabric. A new procedure is proposed to produce samples with target Dr using the discrete element method (DEM). DEM simulations were carried out using spherical particles. Particulate scale analysis of variation of stress reduction factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…All papers were subject to the standard, rigorous peer review required for publication in Computers and Geotechnics, resulting in the final 10 papers in this special issue. The papers themselves can be classified into 4 categories: (i) Developments in the DEM method (Duriez and Bonelli (2021), Li, Zhang and Duan (2020) advance understanding of material behaviour ( (Otsubo et al, 2020), (Ahmadi et al, 2020), and (Huang et al, 2020)), (iii) Use of DEM to simulate problems involving coupled fluidparticle interactions (Hu et al, Li, Zhang and Duan (2020), Xu and Dong (2021), Yamashiro and Tomac ( 2021)) (iv) Application of DEM to boundary value problems (Pol andGabrielli (2021), , Zhang et al, (2021)). These categories broadly reflect our analyses of DEM papers in Computers and Geotechnics, however there is a clear interest in coupled CFD-DEM simulations in this special issue.…”
Section: Figure 1: Data Publication Of Dem-related Papersmentioning
confidence: 99%
See 3 more Smart Citations
“…All papers were subject to the standard, rigorous peer review required for publication in Computers and Geotechnics, resulting in the final 10 papers in this special issue. The papers themselves can be classified into 4 categories: (i) Developments in the DEM method (Duriez and Bonelli (2021), Li, Zhang and Duan (2020) advance understanding of material behaviour ( (Otsubo et al, 2020), (Ahmadi et al, 2020), and (Huang et al, 2020)), (iii) Use of DEM to simulate problems involving coupled fluidparticle interactions (Hu et al, Li, Zhang and Duan (2020), Xu and Dong (2021), Yamashiro and Tomac ( 2021)) (iv) Application of DEM to boundary value problems (Pol andGabrielli (2021), , Zhang et al, (2021)). These categories broadly reflect our analyses of DEM papers in Computers and Geotechnics, however there is a clear interest in coupled CFD-DEM simulations in this special issue.…”
Section: Figure 1: Data Publication Of Dem-related Papersmentioning
confidence: 99%
“…This paper along with the contribution by Li, Zhang and Duan (2020) From a geomechanics perspective, one motivation to use DEM that it enables us to study the origins of the complexity of the mechanical behaviour of soil in physical regimes ranging from quasi-static to dynamic. There are three examples of use of DEM in this way in this special issue: Ahmadi et al, (2020) focused on internal stability, Otsubo et al, (2020) analyzed wave propagation and Huang et al, (2020) considered liquefaction. Otsubo et al, (2020) investigated the anisotropy of small-strain stiffness by simulating elastic wave propagation in granular soils under a K0 stress-state; they considered particles with different aspect ratios and varied the particle major axis orientation.…”
Section: Figure 1: Data Publication Of Dem-related Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…The mass proportion of fine grains (usually named fine content or simply FC) has a significant effect on the mechanical properties of grain assemblies, and the role of fine grains in mixtures has received an acute attention in the literature (Lade and Yamamuro 1997;Monkul and Ozden 2007;Papadopoulou and Tika 2008;Cabalar 2011;Jiang et al 2015;Zhou et al 2018;Rahman et al 2011;Shi et al 2019;Shi et al 2021;Thevanayagam et al 2002;Cao et al 2021;Ng et al 2017;Zhou et al 2018;Ueda et al 2011). From a numerical point of view, discrete element methods (DEM) stand as an interesting tool to access to detailed and extensive information at grain scale level and improve the understanding of the mechanical role of fine grains in granular materials (Ahmadi et al 2020;Gong and Liu 2017;Gong et al 2019a and2019b). For instance, DEM simulations showed that fine grains exhibit a smaller effective stress than coarse grains in gap-graded materials with low fine contents (Shire and O'Sullivan 2013;Shire et al 2014).…”
Section: Introductionmentioning
confidence: 99%